PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE THE POWER OF TWO TERHADAP HASIL BELAJAR IPS SISWA KELAS V SD NEGERI 125 PEKANBARU - Nur Khairanisa Nur Khairanisa; Otang Kurniaman; Neni Hermita (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2019)
This research was conducted because f the low learning outcomes of IPS student. This research was conducted at Pekanbaru Public Elementary School in class Va. There were 20 student. This type of research is a pre-experiment, one type of pretest-posttest design, which is an experiment conducted on the one group without comparison. Based on the result of the study, it was found that the average score of the learning outcomes before the treatment (pretest) was 47,5 while the average test of learning outcomes after treatment (posttest) was 87, and the result of hypothesis testing used the t-test with t = 18,711 and t table = 2,093, it is concluded that tcount>ttable, then Ho is rejected, which means there are differences in social studies learning outcomes between before and after appliying the type of the power of two cooperative learning model. This shows that there is the influence of the cooperative learning model of the power of two type on the learning outcomes of social studies at Elementary shcool 125 Pekanbaru.